Implementation of the Control Algorithm of the Variable Structure Controller in the Electromechanical Servo System - Šulčius, N.; Geleževičius, V. A. (Elektronika ir Elektrotechnika, 2006)
The electromechanical servo drive with variable structure velocity controller commanded by Fuzzy logic based control law (PI-PPI) switching device is developed and investigated. Fuzzy logic device is used for P control law duration time definition in dependence on the static load level of the drive. Applied Fuzzy logic control method allows ensuring optimal dynamical quality (defined by ITAE criterion) of the control process independently on the drive load conditions. Two types (Mamdani-type and Sugeno-type) Fuzzy logic devices for P control law duration time definition have been designed and investigated. Presented modeling results of the electromechanical servo drive confirm suitability of the proposed control method. Ill. 7, bibl. 6 (in English; summaries in English, Russian and Lithuanian).